MOLECULAR CHARACTERIZATION OF SOME ENIGMATIC LOWER DEVONIAN FOSSILS - SOME ANSWERS, MORE QUESTIONS - Abbott G.D.; Ewbank G.; Edwards D.; Wang G.Y. (My University, 1998)
The coalified remains of three extinct nonvascular Lower Devonian plants (Prototaxites Dawson, Pachytheca Hooker, and Parka Fleming) have been analysed using flash pyrolysis-gas chromatography-mass spectrometry, FTIR, and 13C solid-state NMR. The affinities of these fossils are unknown and their habitats remain conjectural. Host rock lithology and grain size correlate with the state of morphological and chemical preservation of Prototaxites. The flash pyrolysates of well-preserved Prototaxites and Pachytheca were dominated by aromatic hydrocarbons and alkylphenols. Given their resistance to compression when compared with associated lignified vascular plant fossils, it is possible that Prototaxites and Pachytheca contained an extinct polyphenolic structural biomacromolecule that was a failed experiment during terrestrialization. Precise affinities for the enigmatic fossils Prototaxites, Pachytheca, and Parka are still to be confirmed, although Prototaxites and Pachytheca are chemically distinct from Parka.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская